Analisis Kualitas Air Permukaan Sungai Brantas Berdasarkan Parameter Fisik dan Kimia - Ahmad Iqbal Addzikri; Firra Rosariawari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The Brantas River is a river that plays an important role in supplying the largest raw material for drinking water in the East Java region. Raw water sourced from the Brantas River must have gone through a proper water treatment process and must comply with the requirements for drinking water quality standards stipulated in Permenkes No. 492 of 2010 concerning Drinking Water Quality Requirements. This study aims to determine the surface water quality of the Brantas River based on measurements of physical parameters (turbidity, temperature, DHL, and TDS) and chemical parameters (pH, and residual chlorine) before and after the water treatment process. This study uses a quantitative method on the basis of observation. The research subjects taken were data measuring surface water parameters of the Brantas River from April 2022 to March 2023 before and after the water treatment process. The results showed that there was a difference in the average value before and after the water treatment process for turbidity of 374.8, temperature of 0.06, DHL of 13.5, TDS of 18.58, pH of 0.01, and residual chlorine of 0.27. It is known that all parameters of the surface water of the Brantas River which have gone through a water treatment process meet the drinking water quality standards according to the requirements of Permenkes No. 492 of 2010. And it can be concluded that the quality of drinking water sourced from the surface water of the Brantas River is good and can be distributed to the community.